Mixing of two streams, steam and water, in a converging nozzle - Aybar, Hikmet Ş. (My University, 2000)
Mixing of two fluid streams can be seen in many applications in chemical processing and energy generation industries. The supersonic steam blows into the cold water in the mixing nozzle. When the steam condenses, steam transfers to water heat and mass (because of the temperature difference and condensation) and momentum (because of the velocity difference). The condensation should be fully completed before the end of mixing nozzle. Thus, the length of the mixing nozzle is important parameter. After the condensation is completed, the flow is single phase, that is, liquid water, and the subsonic water flows in the converging nozzle. In this study, the mixing of the supersonic steam and subsonic water in a converging nozzle is investigated. The problem is modeled using one-dimensional continuity, momentum and energy equations, and solved numerically. For the calculation of the rate of condensation, a correlation for the contact heat transfer coefficient is used.